"My Lady Tells Me I'm Good Woman…": a Bulgarian Female Migrant's Life-Story Between Assistance Relations and Care Practices. Issue 4 (4th July 2017) - Zito, Eugenio
Abstract : In this article, I report on a Bulgarian female migrant caregiver's "life-story, " especially focusing on her relationship with an old Italian woman, on the care practices performed in her favor in Italy, and on her daughter and parents still living in Bulgaria. I chose to do it by means of an anthropological approach based on experience as field of mediation between personal dimensions and historical and social processes and therefore centered on the body conceived as historical product, the influence of political and social forces on shaping human lives, and finally interest in the specific link between bodies and work. From this analysis, based on language and narratives, I think useful cultural aspects may emerge about "gender" and care practices, regarding the two women linked by an assistance relationship, and the activities/strategies used by the Bulgarian caregiver to fulfill her family obligations.